PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Setyowati Subroto (Fakultas Ekonomi Universitas Islam 45, 2018)
The aim of this study is to analyze the effect of training to employee performance; analyze the effect of motivation to employee performance and analyze the effect of training and motivation to employee performance. This research was conducted in PT Tegal Shipyard Utama which engaged in ship building industry. The population of this study is 30 employees and using saturated samples technique, because all members of the population used as samples. A questionnaire consisting of items statement about training, motivation and employee performance using data collection techniques. Validity test results tha all indicators are valid and reliability test results shows that each variable is reliable. In addition, the data analysis technique used is multiple linear regression, because it tested more than one independent variable. The result of this research there is influence of training to employees performance; there is no influence of motivation on employee performance and there is influence of training and motivation to employee performance.